1999
DOI: 10.1128/jb.181.3.849-857.1999
|View full text |Cite
|
Sign up to set email alerts
|

Poly-3-Hydroxybutyrate Degradation in Rhizobium (Sinorhizobium) meliloti : Isolation and Characterization of a Gene Encoding 3-Hydroxybutyrate Dehydrogenase

Abstract: We have cloned and sequenced the 3-hydroxybutyrate dehydrogenase-encoding gene (bdhA) from Rhizobium (Sinorhizobium) meliloti. The gene has an open reading frame of 777 bp that encodes a polypeptide of 258 amino acid residues (molecular weight 27,177, pI 6.07). The R. meliloti Bdh protein exhibits features common to members of the short-chain alcohol dehydrogenase superfamily. bdhA is the first gene transcribed in an operon that also includes xdhA, encoding xanthine oxidase/dehydrogenase. Transcriptional start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 84 publications
1
20
0
Order By: Relevance
“…It is known for other microorganisms that BdhA catalyses the first steps of PHB granule degradation (28). In this study, the MS1 strain indeed showed a higher accumulation of PHB granules than its parental strain suggesting a role bdhA in the metabolism of this important source of energy.…”
Section: Discussionsupporting
confidence: 53%
“…It is known for other microorganisms that BdhA catalyses the first steps of PHB granule degradation (28). In this study, the MS1 strain indeed showed a higher accumulation of PHB granules than its parental strain suggesting a role bdhA in the metabolism of this important source of energy.…”
Section: Discussionsupporting
confidence: 53%
“…BioS transcription was also at a maximum in the presence of nanomolar amounts of biotin [7,8]. To our knowledge the bdhA gene, which is co‐transcribed with the xdhA gene [9], is the second identified S. meliloti locus which is regulated by biotin on a transcriptional level and not linked to biotin synthesis.…”
Section: Resultsmentioning
confidence: 85%
“…A comparison of the bioS and bdhA 5′ regions containing the identified promoters of both genes revealed the presence of common elements in both DNA regions [8,9]. One GNGCATTTGCNC motif consisting of 10 nucleotides (eight identical in both promoters) was detected immediately upstream of the −10 regions in both promoters.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations